Refined analysis of the Speech-to-Speech Synchronization task reveals subharmonic synchronization - Bross, Simon; Hofmann, Andrea; Schneider, Kathleen; Wartenburger, Isabell (Frontiers in Neuroscience, 2025)
The Speech-to-Speech Synchronization task is a well-established behavioral approach to assess individual differences in auditory-motor synchronization. In this task, participants listen to a series of syllables that progressively increase in frequency, while simultaneously whispering the syllable /ta/ to synchronize with the rhythm of the incoming syllables. In our study, we replicated the bimodal distribution of high- and low-synchronizers in a sample of native German speakers. We present a refined analysis pipeline based on existing analysis scripts, address minor task-related issues and observations, and incorporate new analysis features such as the removal of silent gaps. Crucially, our analysis revealed that (sub-)harmonic interactions can emerge during various stages of synchronization and its assessment, obscured by the synchronization measurement. Subharmonic synchronizers were found to produce the /ta/-syllables to only every second or third incoming syllable which can result in deceptively high Phase Locking Values, thus challenging the conceptualization of low- and high-synchronizers. Our data analysis is available at OSF.